PKM. SMP NEGERI 3 KEDIRI DALAM PELATIHAN PEMBUATAN MODUL BERORINTASI SOAL HOTS UNTUK MENINGKATKAN SDM GURU - I Komang Sukendra; Putu Dessy Fridayanthi; Ida Ayu Agung Ekasriadi; Gusti Ayu Made Puspawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2022)
Modules are learning tools or facilities that contain material that aims to enable students to learn independently or with teacher guidance in teaching and learning activities and ways to evaluate are designed systematically, and interestingly to achieve the competencies expected to achieve learning objectives. The objectives of implementing PKM are (1) to increase knowledge of making HOTS question-oriented modules, (2) to improve participants' abilities and skills in integrating HOTS question-oriented modules into the learning process, and (3) to improve participants' ability to implement implementation of HOTS question-oriented modules in the learning process. HOTS questions through the learning process at school. The PKM program is carried out using the method of outreach, training, guidance, and assistance to participants regarding the creation of HOTS question-oriented modules. The main target in this activity is the teachers of SMP Negeri 3 Kediri, Tabanan Regency. Socialization and mentoring activities were carried out by SMP Negeri 3 Kediri by a team of PKM lecturers from PGRI Mahadewa Indonesia University. The results obtained in the PKM program activities were (1) the participants' knowledge in making HOTS question-oriented modules increased, (2) the participants' abilities and skills to integrate HOTS question-oriented modules into the learning process, and (3) participants were able to implement the implementation of making HOTS-oriented modules. HOTS questions in the learning process which can increase teacher human resources in making HOTS question-oriented modules.